PMSE-xG – 5G for Programme Making and Special Events - Bühlmeyer, Jonas; Hertlein, Markus; Fischer, Georg (2nd International Conference on Signals and Systems 2018 (ICSigSys 2018), 2018)
This paper provides a short overview over the prerequisites for the use of 5G for Programme Making and Special Event (PMSE). These will be shortly discussed in the context of the current development of 5G and the German research and development (R&D) project PSMExG. In the project PMSE-xG different use cases of PMSE were examined and demonstration models will be created. This paper focuses on the use of 5G for broadband, low latency and ultra-reliable video streaming in production scenarios like motion picture or television studios. For a first attempt 4G+ software defined radio (SDR) solutions are used to measure the critical parameters and to emphasize the important aspects. After the abstract some general information about the project will be given and the project is further introduced. Subsequently the project partners shall be introduced. Then the different use cases will be presented in short. Afterwards the high data rate streaming will be discussed in focus. Some measurements with two different Software Defined Radio (SDR) platforms are presented then. These results will be discussed before the result will be summariz
Keywords: PMSE-xG; PMSE; 5G; LTE; 4G; SDR; USRP; MIMO; Networking; Communications